Enhancement of transparent hydrogel sanxan production in Sphingomonas sanxanigenens NX02 via rational and random gene manipulation. (1st June 2018) - Wu, Mengmeng; Shi, Zhong; Tian, Xuefeng; Shen, Yaqi; Qu, Jianmei; Dai, Xiaohui; Wei, Weiying; Li, Guoqiang; Ma, Ting
Highlights: An engineered strain was constructed via rational and random gene manipulation. The yield of pure sanxan produced from strain NXdP was 42.5% higher than NX02. The total precipitable material (TPM) produced from NXdP was PHB free sanxan. The light transmittance of TPM from NXdP was much higher than that from NX02. The Zero-shear viscosity of TPM from NXdP showed 60% higher than that from NX02. Abstract: Polymer sanxan is a novel microbial polysaccharide produced by Sphingomonas sanxanigenens NX02, which can produce poly-3-hydroxybutyrate (PHB) simultaneously. A strategy of combining rational and random gene manipulation was investigated to improve the yield of sanxan. Several crucial PHB biosynthesis genes were deleted through homologous recombination, then the PHB-deficient mutant was treated with plasma mutagenesis to obtain NXdP, an engineering strain. Ultimately, the yield of purified sanxan produced by strain NXdP increased from 14.88 ± 0.83 g/L to 21.20 ± 0.38 g/L in a 5 L bioreactor, while the cell dry weight (CDW) was decreased from 9.61 ± 0.14 g/L to 3.12 ± 0.15 g/L. The total precipitable material (crude sanxan) produced from NXdP showed higher zero-shear viscosity, light transmittance, and greater gel strength than that from NX02 due to the enhancement of its purity. The engineering strategies explored here are useful for engineering cell factories to produce other valuable metabolites.